Co-designed farming scenarios show that vegetation is more effective than drainage regulating water excess in the inner Argentinean Pampas - López, Sebastián; Videla Mensegue, Horacio Rogelio; Guillen, Nicolás Federico; Alvarez, Javier; Corigliano, José; Macchiavello, Alejandra; Romero Verastegui, Betsy; Kroon, Timo; Veldhuizen, Albert A.; Salafia, Analía Grisel; Blanco, Paola; Canale, Alejandra; et al. (Elsevier, 2025)
Study region: La Picasa endorheic basin (6 820 km²), Inner Argentine Pampas, one of South America’s most productive rain-fed plains. Study focus: We evaluated how land-use change, rainfall variability and drainage infrastructure control shallow-groundwater behaviour in ultra-flat landscapes. The Soil Water Balance (SWB) crop model was linked to the iMOD groundwater model through a one-way coupling to simulate daily water-table dynamics (2009–2019) under four stakeholder-defined scenarios: current practice (E0), agricultural intensification (E1), pasture intensification with + 20 % perennial cover (E2) and a six-fold drainage-network expansion (E3). New hydrological insights for the region Pasture intensification deepened the median water table by ∼0.9 m and halved the area with depths < 1 m, outperforming intensified cropping (–0.3 m) and extensive drainage (negligible basin-wide effect). Drainage channels acted only as local, short-term buffers during extreme floods. Inter-annual rainfall variability remained the dominant driver of groundwater fluctuations, yet adaptive land-use mixes can increase storage ahead of wet periods. Results indicate that nature-based vegetation strategies are more effective and sustainable than additional “grey” infrastructure for regulating water excess in the Inner Pampas and similar dry-plain agro-ecosystems.